The Issues of the Performance Appraisal Systems in Chinese State-owned Banks Case Study from China - Liao, Linge (2018)
This dissertation provides an insight of performance appraisal (PA) into Chinese state-owned banks and aims to examine its existing issues. A case study of a Chinese state-owned bank, ‘Agriculture Bank of China' is conducted here to complete this qualitative research combined with semi-structured interviews to collect research data. The findings of this case study implicate that there are four main challenges Chinese state-owned banks often meet when implementing PA systems. For the first one, it is concerned with the communication between supervisors and subordinates and the feedback returned to subordinates. Both of them are limited in state-owned banks. Secondly, for some managers, it is difficult for them to set reasonable targets. Most of the time, targets are set either too high or too low. The third issue is related to the fairness of the assessments in PA systems, which are often bias and inaccuracy. And finally, it is showed that the commitment to pre-set rewards is often not taken into practice. Then, in addition to the recommendation of further development in improving managers' abilities and loosen banks’ budget policies. The further research is suggested to explore the scope of cases and to use mixed research. Furthermore, the issues of PA systems in Chinese private commercial banks is also suggested to be a valuable topic in the future research.